Contemporary Christian issues - Ramientos, Nene (Quezon City New Day, 1982)
This book discusses cooperative evangelism and the effects of evangelism to the world. It also tackles the mission of the church in the Asian realm and how the Church affects institutions.
Keywords: Evangelistic work; Christianity; Leadership (in religion, folk-lore, etc.)